Advanced Supervision in Educational Management: Differences Between Supervision, Accreditation, Inspection, Collaboration, Evaluation, And Quality Assurance - Adeoye, Moses Adeleke (ASEAN Journal of Educational Research and Technology, 2022)
The paper examines the differences between different supervision models in educational management including supervision, accreditation, inspection, collaboration, evaluation and quality assurance. By understanding the distinctions between these different approaches, educational managers can choose the most appropriate strategies for improving school performance. The research will also contribute to the development of a robust evidence base for advanced supervision in educational management. The study compares and contrasts the different models of advanced supervision in educational management and their effectiveness in improving educational outcomes. Finally, the study will contribute to the existing literature on advanced supervision in educational management and provide a valuable reference for scholars, practitioners, and policymakers.